Research on the Application of the Model Order Reduction Algorithm in Designing a Robust Controller for the Balance System of a Self-Balancing Two-Wheeled Bicycle - Trung, Ngo Kien; Tham, Nguyen Thi; Diep, Trinh Thi; Ngoc, Vu Thi Anh; Nguyen, Hong Quang (Engineering, Technology & Applied Science Research, 2025)
This paper focuses on the design analysis and control of a Self-Balancing Two-Wheeled Bicycle (SBTWB) model. The difficulty of the two-wheeled bicycle balance control problem is that the two-wheeled bicycle model is uncertain and is continuously affected by disturbances. Many different control methods have been proposed to design an SBTWB balance controller, but the most suitable algorithm is the robust control algorithm. However, the robust controller of an SBTWB is often complex and of higher order, which affects the quality of the control process. This study introduces a Model Order Reduction (MOR) algorithm based on the preserving dominant poles and applies this algorithm to simplify the 15th order robust controller of the balance control system of an SBTWB. Through comparison and evaluation, it is shown that the 5th-order controller or the 4th-order controller can replace the 15th-order robust controller. Through a simulation of the control system using the 4th-order controller, it is demonstrated that the proposed 4th-order controller ensures a stable balance of the SBTWB, while the 4th-order controllers according to other order reduction methods cannot maintain the balance of the SBTWB. The simulation results show the effectiveness of the order-reduction algorithm based on the conservation of dominant pole points and the robust control algorithm for the SBTWB.